FACTORS AFFECTING NURSE ANXIETY IN ROLE AS A CAREGIVER DURING THE COVID-19 PANDEMIC - Yurike Septianingrum; Andikawati Fitriasari; Erika Martining Wardani (Nurse and Health: Jurnal Keperawatan, 2021)
Background: During the Covid-19 outbreak, health workers, especially nurses, are vulnerable to potential psychological symptoms such as anxiety, which can prevent nurses from carrying out their role as caregivers in health services (Lai et al., 2020; Shanafelt et al., 2020). Objectives: The purpose of this study is to analyze the factors that can influence the anxiety of nurses in playing the role of caregiver during the Covid-19 pandemic. Methods: This is a cross-sectional study with a population of all nurses who met the inclusion criteria as much as 105 nurses. The research sample was selected through stratified random sampling and obtained 84 nurses. This research was conducted at RSI Jemursari Surabaya from June until September 2020. The research instruments used in this study were the demographic observation sheet, knowledge questionnaire, and the Hamilton Anxiety Rank Scale (HARS). Data analysis used Pearson chi-square test and multivariate logistic regression. Results: The results of the Pearson Chi-square test showed that of all the factors studied, only age (p = 0.004), availability of personal protective equipment (p = 0.002), and knowledge (p = 0.017) influenced nurses' anxiety. The results of the analysis using multivariate logistic regression test showed that the factor that most influenced nurses' anxiety was the availability of personal protective equipment (p = 0.001; OR = -3.062). Conclusion: Younger nurses, inadequate personal protective equipment, and less knowledgeable nurses were at high risk for more severe anxiety. Regular observation of the psychological condition of nurses and the fulfillment of the need for personal protective equipment is needed to prevent increased anxiety in nurses.